Maritime Transport Safety - Atika, Aulia Ika; Triwahyuni, Siti Nurlaili; Tuib, Anwar (IWTJ : International Water Transport Journal, 2020)
This study aims to analyze the technicalities of public shipping from the aspects of ship construction and stability, to analyze non-technical factors that cause accidents, to find efforts to improve shipping safety in supporting policies and strategies related to the roadmap to zero accidents. The research method used to calculate stability and strength is a quantitative empirical method equipped with interviews and questionnaires. The research locations are Makassar, Jakarta, Semarang, Surabaya, Kupang, Sampit, and Jambi. The sample for the empirical method is the ship 100-150 GT which predominantly has an accident, while for interviews and questionnaires used 140 respondents. Data were analyzed by factor analysis and SWOT. The results showed that the vessel stability arm, stability arch area, and metacentra height (MG) met the criteria of the International Martim Organization (IMO) and were above the required conditions. Phinisi fleets are seaworthy from the aspect of stability. Ships have high feasibility to sail. The factor analysis found seven non-technical factors, namely duties and responsibilities, competence in the field of human resources in the field of ship safety, company commitment, shipping navigation equipment, crew competence, ship maintenance and loading systems, as well as recruitment and training. Therefore, the strategy to improve safety includes intensifying the ship skills and maintenance training program, improving shipbuilding quality standards, performance of ship navigation facilities, and seeking to implement technical standards for ship safety.